Importance of String Matching in Real World Problems (International Journal of Engineering and Computer Science, 2017)
String Matching is the classical and existing problem, despite the fact that the real world aspects belonging to the research field of computer science. In this domain one or several strings called “Pattern” is to be searched within a well-built string or “Text”. String matching strategies or algorithms provide key role in various real world problems or applications. A few of its imperative applications are Spell Checkers, Spam Filters, Intrusion Detection System, Search Engines, Plagiarism Detection, Bioinformatics, Digital Forensics and Information Retrieval Systems etc. This paper is inclusive of analyzing nutshells about string matching along with its long-ago contributory details in an assortment of real world applications.